Evaluation of Collection Development and Management in Selected University Libraries in Ogun State, Nigeria - Awojobi, Esther Abosede; Uthman, Kikelomo Olubunmi (Ghana Library Journal, 2022)
Collections of five university libraries in Ogun State, Nigeria were evaluated using SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. Results showed that the libraries have strengths in having a collection development policy, users’ involvement in collection development, balanced, relevant and high-quality collections and up-to-date online databases. Lack of weeding policy and non - participation in the consortium are weaknesses in three libraries, opportunities include the use of other library resources, technology, open access resources, and acquisition through the Tertiary Education Trust Fund (Tetfund) in the government-owned institutions while the high cost of online subscriptions, other information services providers, inadequate funding of collection development in four libraries, reliance on Tetfund, gifts and exchange by public universities constitute threats. Findings further revealed no significant difference between collection development of public and private university libraries (t(74) = 0.20, p> 0.05). The study recommends the development of a weeding policy that must be adhered to as well as collaboration amongst libraries.